Application of Allot Secure Service Gateway for WAN Network Bandwidth Management at PT. Bank Permata Tbk - Dimas Trisna Putra Pambarep; Sussana Dwi Yulianti Kusuma (Universitas Pendidikan Nasional, 2024)
As is generally experienced by large companies that have a large number of branches and centralized applications, PT. Bank Permata Tbk currently has WAN Bandwidth that manages links and the complexity of current applications and Protocols. However, the application and observation of the Bandwidth settings has not been maximized. If these problems are not regulated, it is feared that this will interfere with the performance of PT. Bank Permata Tbk which in the end will be able to reduce the level of business competition ability when compared to other Top companies that become its competitors. The research method used in this research is the HTB (Hierarchical Token Bucket) method. The HTB method is a method that functions to regulate the distribution of Bandwidth, the division is carried out in a hierarchy which is divided into classes to make Bandwidth Management easier. At this stage, the problem that will become the research object of the problem formulation is the absence of structured reports for Bandwidth usage in each branch. In the analysis of this system it can be concluded that PT. Bank Permata Tbk does not yet have a structured report for Bandwidth usage at each branch and without any special limitations on Bandwidth. And with this problem, the branch application that is used does not run optimally. With the implementation of Bandwidth Management using the Allot Secure Service Gateway on the WAN network of PT. Bank Permata Tbk so that it can produce structured reports and monitor Traffic Bandwidth from both branches to branch applications.